A advocacia extrajudicial como instrumento de efetivação do direito fundamental de acesso à justiça na perspectiva da desjudicialização - Mariante, Thalita Lyzis Silva Viana (2024)
Conflicts inevitably arose from social interactions, reflecting the ongoing development of human society. In this context, Law emerged as a science to regulate these relationships and promote social peace, without necessarily resorting exclusively to the Judiciary. Each conflict was unique and non-replicable, with its own peculiarities, requiring specific treatment that took into account the individual needs of the parties involved. It was the responsibility of the manager to identify these needs and interpret the information presented by the parties, or the lack thereof. Hence, there arose a pressing need for a legal profession prepared and equipped with the necessary conditions to effectively manage the social conflicts brought before it. The legal professional should be capable not only of diagnosing the conflict but also of selecting and implementing appropriate methods of resolution. When examining the trajectory of legal science in attempting to resolve conflicts, we encounter a notable disregard for the essential particularities that were fundamental to proper conduct and resolution. This manifested in the application of generic and inadequate solutions, often based on the theoretical common sense of jurists, who considered judicialization as the best or only way to resolve conflicts. This approach contributed to the crisis faced by the Judiciary, unable to efficiently handle the quantity and complexity of social demands. Simultaneously, we observe a growing global trend towards de-judicialization, evidenced by initiatives such as the UN's Agenda 2030 and Global Access to Justice, alongside normative developments in Brazil that facilitated the use of alternative methods of conflict resolution. Faced with these scenarios, it was crucial for the legal profession to fulfill its constitutional mission of promoting justice through the prevention and resolution of conflicts, adapting specific solutions to the particularities of each case. To effectively realize the fundamental right of access to justice through a robust extrajudicial legal practice, it was imperative to overcome identified obstacles: the litigious culture in legal education, the predominance of judicialization in the Brazilian justice system, and society's lack of awareness about extrajudicial alternatives. This required coordinated actions among legal courses, public authorities, private entities, and legal professionals to transform legal education, implement structural changes in the justice system, and educate society about alternative methods of conflict resolution